2001
DOI: 10.1891/0889-8391.15.3.253
|View full text |Cite
|
Sign up to set email alerts
|

Are the Short and Long Forms of the Young Schema Questionnaire Comparable and How Well Does Each Version Predict Psychopathology Scores?

Abstract: Young’s Schema Questionnaire (YSQ; Young & Brown, 1994) was developed to measure schemas that may need to be modified during therapy. This study examines whether the long and short forms of the YSQ produce comparable scores in a heterogenous group of psychiatric outpatients. The study also looks at how well each version predicts psychopathology measured by the SCL-90 -R (Derogatis, 1977). The results of this study show that the two versions of the YSQ have similar levels of internal consistency, parallel f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
90
0
2

Year Published

2004
2004
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 113 publications
(99 citation statements)
references
References 0 publications
7
90
0
2
Order By: Relevance
“…Further, this study demonstrated that the YSQ is reliable and possesses satisfactory convergent and divergent validity as shown by its correlations with measures of psychological distress, self-esteem and personality disorder symptoms. Highly similar results have been obtained in subsequent studies that were carried out to examine the factor structure, reliability and validity of the long and short versions of the YSQ (Calvete, Estevez, Lopez de Arroyabe, & Pilar, 2005;Cecero, Nelson, & Gillie, 2004;Lee, Taylor, & Dunn, 1999;Rijkeboer, Van den Bergh, & Van den Bout, 2005;Stopa, Thorne, Waters, & Preston, 2001;Waller, Meyer, & Ohanian, 2001). Finally, using the YSQ, core maladaptive schemas have been successfully identified in patients suffering from various types of psychopathology such as eating disorders (Meyer & Gillings, 2004;Meyer, Leung, Feary, & Mann, 2001;Waller, Dickson, & Ohanian, 2002), anxiety disorders (Dellatre et al, 2004), comorbid anxiety and eating disorders (Hinrichsen, Waller, & Emanuelli, 2004), substance abuse disorders (Brotchie, Meyer, Copello, Kidney, & Waller, 2004;Decouvelaere, Graziani, Gackiere, Rusinek, & Hautekeete, 2002) and aggressionrelated disorders (Baker & Beech, 2004).…”
Section: Introductionsupporting
confidence: 69%
“…Further, this study demonstrated that the YSQ is reliable and possesses satisfactory convergent and divergent validity as shown by its correlations with measures of psychological distress, self-esteem and personality disorder symptoms. Highly similar results have been obtained in subsequent studies that were carried out to examine the factor structure, reliability and validity of the long and short versions of the YSQ (Calvete, Estevez, Lopez de Arroyabe, & Pilar, 2005;Cecero, Nelson, & Gillie, 2004;Lee, Taylor, & Dunn, 1999;Rijkeboer, Van den Bergh, & Van den Bout, 2005;Stopa, Thorne, Waters, & Preston, 2001;Waller, Meyer, & Ohanian, 2001). Finally, using the YSQ, core maladaptive schemas have been successfully identified in patients suffering from various types of psychopathology such as eating disorders (Meyer & Gillings, 2004;Meyer, Leung, Feary, & Mann, 2001;Waller, Dickson, & Ohanian, 2002), anxiety disorders (Dellatre et al, 2004), comorbid anxiety and eating disorders (Hinrichsen, Waller, & Emanuelli, 2004), substance abuse disorders (Brotchie, Meyer, Copello, Kidney, & Waller, 2004;Decouvelaere, Graziani, Gackiere, Rusinek, & Hautekeete, 2002) and aggressionrelated disorders (Baker & Beech, 2004).…”
Section: Introductionsupporting
confidence: 69%
“…Each item is scored on a sixpoint scale, with high scores reflecting unhealthy, maladaptive core beliefs. The internal consistency and discriminative validity of the short 75-item version have been established and are comparable to those of the long version (Waller, Meyer, & Ohanian, 2001), and has been demonstrated to have good clinical and empirical reliability and validity (Cecero et al, 2004;Stopa, Thorne, Waters, & Preston, 2001;Welburn et al, 2002), with empirical support for the hypothesized factors (see, e.g., Cecero et al, 2004). In addition to showing good construct validity in its ability to predict psychopathological and psychiatric symptoms (Stopa et al, 2001;Welburn et al, 2002), the YSQ-S is also suitable for use in non-clinical groups (Cecero et al, 2004;Waller et al, 2001).…”
Section: Core Beliefsmentioning
confidence: 98%
“…Young 2 suggests that a schema with two or more items rated as 5 or 6 is 'clinically significant'. Research 27,28 suggests that the short version has very similar levels of internal consistency, reliability and validity compared with the longer version.…”
Section: Young Schema Questionnaire-short Form (Ysq-s)mentioning
confidence: 99%